Good Practices for Financial Consumer Protection, 2017 Edition - World Bank Group (World Bank, Washington, DC, 2017)
Over the past decade, financial consumer protection has become an increasingly mainstream priority for policymakers. A strong consumer protection regime is key to ensuring that expanded access to financial services benefits consumers, enabling them to make well-informed decisions on how best to use financial services, building trust in the formal financial sector, and contributing to healthy and competitive financial markets. The World Bank’s Good Practices for Financial Consumer Protection (the Good Practices) was developed in 2012 as a contribution to the emerging global set of tools on financial consumer protection. Since then, international guidance and country practices regarding financial consumer protection have substantially evolved. The 2017 Good Practices is designed to serve as a comprehensive reference and assessment tool for policymakers that consolidates the latest research, international guidance, and country examples. A thorough update of the previous edition, this guide expands upon priority areas such as supervisory techniques, effective disclosure, and digital finance, and also emphasizes the practical considerations and tradeoffs that policymakers face when implementing new policies and practices.